Survey Tingkat Pengetahuan Serta Kesiapan Dosen dan Mahasiswa dalam Pelaksanaan Program Merdeka Belajar Kampus Merdeka - Lilis Puspitawati; tatik Rohmawati; Manap Solihat; Inggar Prayoga; Aelina Surya (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2023)
Abstract: The purpose of this survey is to determine the level of knowledge and readiness of lecturers and students in the implementation of the MBKM program and to find out the obstacles in the implementation of the MBKM program. This survey uses a descriptive method and the data is processed using descriptive statistics. The survey was conducted on 1307 respondents consisting of 23 lecturers and 1284 students in the UNIKOM Faculty of Social and Political Sciences (FISIP). The survey results show that lecturers already have an adequate level of knowledge regarding MBKM program policies while students do not yet have adequate knowledge regarding MBKM program policies. Furthermore, the survey results show that lecturers and students are ready to implement the MBKM program because the MBKM program has an impact on increasing the competence, hardskills and softskills of graduates that are relevant to the needs of future users, although the majority of students do not feel confident that they can join the program, but students at FISIP UNIKOM have ready to join the MBKM program. Financial factors, regulations, limited information and human resource capabilities, curriculum adjustments, value conversion and academic information systems, assessments with partners and support from higher education leaders are the biggest inhibiting factors in the implementation of the MBKM program.Keywords: competence, readiness of lecturers and students, MBKM program Abstrak: Tujuan dari survey ini adalah untuk mengetahui tingkat pengetahuan serta kesiapan dosen dan mahasiswa dalam pelaksanaan program MBKM serta mengetahui hambatan dalam pelaksanaan program MBKM. Survey ini menggunakan metode deskriptif dan data diolah dengan menggunakan statistik deskriptif. Survey dilakukan pada 1307 responden yang terdiri dari 23 orang dosen dan 1284 mahasiswa di lingkungan Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UNIKOM. Hasil survey memperlihatkan dosen telah memiliki tingkat pengetahuan yang memadai terkait kebijakan program MBKM sedangkan mahasiswa belum memiliki pengetahuan yang memadai terkait kebijakan program MBKM. Selanjutnya hasil survey menunjukan dosen dan mahasiswa telah siap melaksanakan program MBKM karena program MBKM berdampak terhadap peningkatan kompetensi, hardskills dan softskills lulusan yang relevan dengan kebutuhan pengguna dimasa yang akan datang, walaupun mayoritas mahasiswa belum merasa yakin dapat mengikuti program tersebut namun mahasiswa di FISIP UNIKOM telah siap untuk mengikuti program MBKM. Faktor finansial; regulasi, keterbatasan informasi dan kapabilitas sumber daya manusia; penyesuaian kurikulum, konversi nilai dan sistem informasi akademik; Penjajagan dengan Mitra serta dukungan pimpinan Perguruan Tinggi merupakan faktor-faktor penghambat terbesar dalam pelaksanaan program MBKM.Kata kunci: kompetensi, kesiapan dosen dan mahasiswa, progam MBKM